KONTRIBUSI PENDIDIKAN JASMANI DALAM MEMBENTUK KARAKTER PESERTA DIDIK - - Paiman (Jurnal Pendidikan Jasmani Indonesia, 2013)
Lately the character the young generation of Indonesian is at the level of worrying There are many bad behaviourdone by young people such as juvenile deliquency, drugs, and some uncivililized actions such as corruption, nepotism,tribe conflics. Those are indicated that the moral decadencies happened in all aspects of life. In a wider context,if we cannot improve the condition, this bad behaviours will lead the disintegration of Indonesia as a united nationand united country. This proves the character building of Indonesian shoud have the first priority in developing thecountry especially in the national education system in Indonesia. The good characters of students will influencestudents performannce in learning and its result. The base character of the students are good in spiritual, patriotism,discipline, responsibility, wide point of view, optimism, deep spiritual view, and deep nationalism. Those charactersmust be internalized into every individiual through education in schools and colleges. Physical education as oneof subject at school has strategic role in internalizing the good characters. This can be done through the activity ofgiving advices, simulation and discussion, example in real practice trough games and teaching learning activities.The most effective technique is example. The Indonesian’s proverb says that one example is more effective thanthousands of advices. Trough games and sport activities, teacher can internalize the good characters into student’spersonalities as well as fun.Keywords: Character Building, Students, Physical Education.